Coping with Tensions That Arise from Professional Collaboration Among Street-Level Bureaucrats in the Context of Public Sector Reform - Jalonen, Harri; Laasanen, Miia; Salminen, Jaanet (Taylor & Francis, 2026)
This study examines the tensions arising from collaborationamong street-level bureaucrats (SLBs) in Finland’s nationwidereform of social and health services, with a particular focus onstudent welfare. While the reform aims to integrate services, itrisks creating gaps between education and health professionalsacross different jurisdictions. We employed mixed methods,including document analysis, surveys, and a Delphi panel, toexplore how collaborative tensions manifest and how SLBs uti-lize discretionary practices to cope. Our analysis identifies fourkey tensions: the balance between privacy protection andeffective collaboration, the hierarchical structuring of welfareplanning versus local discretion, sectoral boundaries versusshared responsibility, and children’s rights versus ensuring sup-port. The findings indicate that coping strategies based on aneither-or approach, which separates competing demands, offerlimited capacity for addressing the complexities of the imple-mentation of reform. A both-and approach enables SLBs toacknowledge competing demands and balance them in prac-tice, but may stabilize tensions without transforming collabora-tion. The study underscores the relevance of a more-thanapproach as a reflexive and generative mode of coping. Theapproach enables SLBs to further student welfare by interpret-ing their responsibilities, negotiating meanings, and co-produc-ing support across organizational and sectoral boundariesrather than merely adhering to rules.